2021
DOI: 10.1177/10497323211023449
|View full text |Cite
|
Sign up to set email alerts
|

Successfully Negotiating Life Challenges: Learnings From Adults With Cerebral Palsy

Abstract: Despite facing multidimensional inequalities, some adults with cerebral palsy achieve positive social outcomes (e.g., independent living, employment, and romantic relationships). We interviewed 23 adults (aged 23–47 years) about how they successfully negotiated the challenges of adulthood. Common to all life situations was doing what others (people without cerebral palsy) do. Origins of success lay in their formative experiences (e.g., typical parental expectations with commensurate support and acceptance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The physical environment has been reported as a major barrier to participation in community‐based physical activity for people with CP 7 . A recent qualitative study 34 reported ‘accessible and accommodating environments’ took many forms, including physical access, practical supports, reasonable accommodations/adjustments, and positive attitudes towards disability. Another recent study described the supports required for people with complex CP to successfully access a community‐based exercise facility, and highlighted significant additional time requirements from all stakeholders 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The physical environment has been reported as a major barrier to participation in community‐based physical activity for people with CP 7 . A recent qualitative study 34 reported ‘accessible and accommodating environments’ took many forms, including physical access, practical supports, reasonable accommodations/adjustments, and positive attitudes towards disability. Another recent study described the supports required for people with complex CP to successfully access a community‐based exercise facility, and highlighted significant additional time requirements from all stakeholders 35 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings reinforce the importance of optimizing participation in education of young people with disability, both during mandated school years and beyond. Educational attainment at the level of the individual's capacity is a crucial resource for living, a finding highlighted in a recent studying examining what adults with CP identify as enablers of their success in adulthood ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The young adults with CP in this study reported that lack of confidence was a factor in both their educational and employment participation and that they were not as satisfied with their achievements in life as other Australians. Adults with CP have described needing pathways for developing competence, acceptance and support in school life and skills for making friends ( 45 ): these early formative experiences, along with an expectation that they will take part in society from parents, teachers and themselves, ( 45 ) provide a foundation for adulthood successes, when the needed contextual supports are also in place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the challenges, most persons with CP do wish to be active, fit, and socially connected [ 29 ]. Altering the fitness trajectory of children with CP may require attention to the internal or individual drivers of behavioral change.…”
Section: Altering the Fitness Trajectory Of Children With Cpmentioning
confidence: 99%